Development of Learning Promotion Strategy and System for Working Age Population in the 21st Century - Sungsri, Sumalee; Aimsamang, Cholatit; Nilabutra, Sunan; Sungsri, Pacharawalai; Bunparit, NIttaya (Journal of Humanities and Social Sciences Thonburi University, 2021)
The objectives of this study were: to study policy framework on learning promotion for working age population both in Thailand and other countries, to study the actual state and the desirable state of system and strategy for learning promotion among working age population and to develop a system and strategy for learning promotion among working age population for the 21st century. Documentary study and field research were employed for this study. The samples consisted of 5 policy administrators, 50 administrators and 200 personnel of agencies which provided education for working age population in 10 provinces from every part of the country, 300 working age population, and 5 experts. Research instruments were structured interview forms and questionnaires. Data were analyzed by frequency distribution, percentage, mean, standard deviation and content analysis. The research results proposed a system and strategy for learning promotion among working age population as a whole which included 11 aspects. They were, for example, formulating policy and clearly implementation direction, developing of mapping and working age’s data base, promoting learning interest and lifelong learning habit and establishing guidance centres. Moreover, 5 additional aspects were added to each of formal labour group and informal labour group.